2019
DOI: 10.1523/jneurosci.1895-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptors drive poly(I:C) induced autism-like behavior in mice

Abstract: Maternal immune activation (MIA) is a principal environmental risk factor contributing to autism spectrum disorder (ASD), which compromises fetal brain development at critical periods of pregnancy and might be causally linked to ASD symptoms. We report that endogenous activation of the purinergic ion channel P2X7 (P2rx7) is necessary and sufficient to transduce MIA to autistic phenotype in male offspring. MIA induced by poly(I:C) injections to P2rx7 WT mouse dams elicited an autism-like phenotype in their offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 49 publications
(59 reference statements)
2
32
0
Order By: Relevance
“…The P2X7R has been implicated in several disease conditions, ranging from infections (4) to neurodegeneration (5), from autoimmune diseases (6) to cancer (7). Increasing attention is being paid to the potential involvement of this receptor in neuropsychiatric disorders (8, 9). A substantial effort has been produced by Pharma Industry to develop potent and selective P2X7R blockers for the treatment of chronic inflammatory diseases, but Phase II/III clinical studies failed to provide clear demonstration of the usefulness of P2X7R blockade (10).…”
Section: Introductionmentioning
confidence: 99%
“…The P2X7R has been implicated in several disease conditions, ranging from infections (4) to neurodegeneration (5), from autoimmune diseases (6) to cancer (7). Increasing attention is being paid to the potential involvement of this receptor in neuropsychiatric disorders (8, 9). A substantial effort has been produced by Pharma Industry to develop potent and selective P2X7R blockers for the treatment of chronic inflammatory diseases, but Phase II/III clinical studies failed to provide clear demonstration of the usefulness of P2X7R blockade (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, the offspring born after an MIA pregnancy have ASD-like features, activated brain microglia, and abnormalities in synapse structure for life [71]. Detailed systems analysis of the MIA model has shown that it recapitulates many of the behavioral [68], metabolic [4], immune, microbiome [72], and brain synaptic features [3,73] of children with ASD. In the past, it was shown that toll-like receptor 3 (TLR3) signaling triggered by poly(IC) was important to induce IL6 and IL17, which in turn played key roles in placental and brain in ammatory signaling that preceded the onset of ASD-like behaviors [74].…”
Section: Discussionmentioning
confidence: 99%
“…showed that injection of ATP itself into pregnant females was su cient to produce the post-natal cerebellar Purkinje cell drop out and life-long autism-like behaviors that were indistinguishable from the classical MIA model [73]. Extracellular ATP and its metabolite ADP are both classical purinergic agonists and classical damage-associated molecular patterns (DAMPs) that are released from cells in response to nearly every physical, microbial, in ammatory, chemical, or metabolic stress studied to date [11,14,15,78].…”
Section: Discussionmentioning
confidence: 99%
“…Polyinosinic:polycytidylic acid (poly I:C) can mimic prenatal viral infection. MIA induced by the injection of poly I:C in a mother mouse model revealed that P2X 7 purinergic receptors drive poly I:C-induced autism-like phenotypes such as social deficits and increased self-grooming [ 63 ]. This can induce an increase in inflammatory cytokines and impair neurogenesis, resulting in decreased Purkinje cell number and their density in the cerebellum as well as behavioral abnormalities in the fetal brain [ 101 , 157 ].…”
Section: Asd (Autism Spectrum Disorder) and Adhd (Attention-deficimentioning
confidence: 99%